2009
DOI: 10.1111/j.1600-0714.2009.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

WNT‐5A, but not matrix metalloproteinase 3 or β‐catenin protein, expression is related to early stages of lip carcinogenesis

Abstract: The present results suggest that WNT-5A may be an important marker during initial events of AC malignant transformation, in which non-canonical and canonical Wnt/beta-catenin signaling pathways could be involved. Additionally, WNT-5A might recruit other events in LSCC, such as MMP-3 protein synthesis, as its presence is increased in established malignant processes without beta-catenin dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…8 Upregulation of WNT5a appears conserved in squamous cell carcinomas from different anatomic locations, including the lip, head and neck, and lung, and appears to be an important gene in the tumorigenesis of squamous cell carcinoma. [56][57][58] Upregulation of WNT5a has been identified in many different malignancies, including melanoma and carcinomas from the breast, esophagus, lung, pancreas, and stomach. [59][60][61][62][63] MMP1 was found to be the most overexpressed gene in squamous cell carcinoma in comparison with normal skin (FC ¼ 48.51; Table 2).…”
Section: P53 Signalingmentioning
confidence: 99%
“…8 Upregulation of WNT5a appears conserved in squamous cell carcinomas from different anatomic locations, including the lip, head and neck, and lung, and appears to be an important gene in the tumorigenesis of squamous cell carcinoma. [56][57][58] Upregulation of WNT5a has been identified in many different malignancies, including melanoma and carcinomas from the breast, esophagus, lung, pancreas, and stomach. [59][60][61][62][63] MMP1 was found to be the most overexpressed gene in squamous cell carcinoma in comparison with normal skin (FC ¼ 48.51; Table 2).…”
Section: P53 Signalingmentioning
confidence: 99%
“…The upregulation of MMP3 was validated and identified as a signature in oral squamous cell carcinoma progression (37). Immunohistochemistry revealed the involvement of MMP3 in the events correlated with lip SCC (38). Although not validated, MMP3 was found to be upregulated in LSCC and associated with the development of invasion (39).…”
Section: Discussionmentioning
confidence: 99%
“…These results are contrary to our expectations at the time of planning this study; we expected that Wnt protein would show more prominent IHC staining in IP with dysplasia or IP with SCC. Wnt-1 was selected as a candidate marker based on a study performed in 2008 by Xavier et al , 17 who reported that Wnt protein was not expressed in normal epithelium but was highly expressed in early-stage lip cancer. However, another study presented contradictory findings, that Wnt-1 was concurrently expressed in normal tissue and cancer tissue of colorectal epithelium and that normal epithelium showed stronger staining than cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the canonical pathway, Wnt signaling plays a key role in signal transduction, and without Wnt signaling intracellular ␤-catenin is proteolytically degraded by a protein complex. 17 However, in the presence of Wnt signaling, the function of the degradation complex is inhibited and the intracellular level of ␤-catenin increases, which results in intracellular accumulation and nuclear translocation of ␤-catenin. 18 Translocated ␤-catenin can initiate transcription of several target genes, e.g., cyclin D1, which results in progression toward malignancy.…”
mentioning
confidence: 99%